Islamic Education Institutions During The Bone Kingdom Period (Study of The Role of Andi Mappanyukki Sultan Ibrahim Bone Kingdom XXXII) - Abubakar Abubakar; Bahaking Rama; Sattu Alang; M. Shabir Umar (Universitas Darussalam Gontor, 2023)
The existence of an educational institution is considered to be very influential on the level of understanding and practice of Islamic teachings during the time of Andi Mappanyukki Sultan Ibrahim Kingdom Bone XXXII. This paper tries to trace the role of Andi Mappanyukki Sultan Ibrahim in developing Islamic educational institutions in the Kingdom of Bone and Islamic educational institutions during the time of Andi Mappanyukki Sultan Ibrahim. This type of research is a qualitative field through observation, interviews, documentation, and reference searches. The results of this study indicate that the role of Andi Mappanyukki in forming Sultan Ibrahim in developing Islamic institutions in the Bone Kingdom included socio-religious organizations, educating the Bone kingdom, bring scholars, and Islamic educational institutions. Informal education at the time of Andi Mappanyukki had formal Islamic educational institutions namely al-Madrasah al-Amīriyyah al-Islamiyyah Watampone, non-formal Islamic education institutions were recitations at the Old Mosque (al-Mujahidin), Watampone Great Mosque, Cabalu Mosque, Palakka Mosque, Macege Mosque, Awangpone Mosque, Cenrana Mosque, and the Ulama's House. Relics of the past or commonly called the culture of the end, is a very important thing to know the behavior and activities of humans in their time.